Water Footprint Produksi Tanaman Melon pada Sistem Budidaya Hidroponik dan Konvensional - Fadil Rohman; Tri Rini Kusparwanti; Refa Firgiyanto; Rindha Rentina Darah Pertami; Edi Siswadi; Muhammad Zayin Sukri; Hanif Fatur Rohman; Gallyndra Fatkhu Dinata; Eliyatiningsih Eliyatiningsih; Anggita Rizky Fadilah (Universitas Khairun, 2025)
Water use efficiency is a critical issue in melon production, particularly under greenhouse cultivation systems. This study aimed to compare the water footprint of melon (Cucumis melo L.) production under hydroponic and conventional cultivation systems. The experiment was conducted at the Teaching Factory Smart Greenhouse, Politeknik Negeri Jember, from March to June 2023. Each cultivation system consisted of 30 sampled plants. Both systems applied drip irrigation with a nutrient solution concentration of 1400 ppm. Water footprint was calculated following Hoekstra’s method, considering only the blue water footprint, while green and grey components were assumed to be zero due to the protected greenhouse environment. The results showed that the conventional system produced greater vegetative growth, earlier generative phase development, and higher fruit diameter and weight than the hydroponic system. However, the water footprint of the conventional system was significantly higher. Differences in water footprint were mainly attributed to differences in planting area per plant, which affected plant water use calculated as evapotranspiration multiplied by planting area. The hydroponic system demonstrated higher water use efficiency per unit yield.